2018
DOI: 10.1002/bies.201800075
|View full text |Cite
|
Sign up to set email alerts
|

The LKB1‐AMPK and mTORC1 Metabolic Signaling Networks in Schwann Cells Control Axon Integrity and Myelination

Abstract: The Liver kinase B1 with its downstream target AMP activated protein kinase (LKB1-AMPK), and the key nutrient sensor mammalian target of rapamycin complex 1 (mTORC1) form two signaling systems that coordinate metabolic and cellular activity with changes in the environment in order to preserve homeostasis. For example, nutritional fluctuations rapidly feed back on these signaling systems and thereby affect cell-specific functions. Recent studies have started to reveal important roles of these strategic metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 111 publications
3
29
0
Order By: Relevance
“…The AMPK/ PGC1α pathway is regulated by many upstream signalling molecular. Several lines of evidence support the involvement of AMPK in mediating the beneficial effects of GLP-1 or GLP-1R 9,44,47,48. Ourresults demonstrated that sitagliptin could activate AMPK/PGC1α pathway.…”
supporting
confidence: 74%
“…The AMPK/ PGC1α pathway is regulated by many upstream signalling molecular. Several lines of evidence support the involvement of AMPK in mediating the beneficial effects of GLP-1 or GLP-1R 9,44,47,48. Ourresults demonstrated that sitagliptin could activate AMPK/PGC1α pathway.…”
supporting
confidence: 74%
“…While not all reductions reached statistical significance, the combined effect of decreasing several could significantly reduce astrocyte glucose uptake and glycogen synthesis, reduce lactate production, and reduce lactate export through MCT1. This is consistent with findings that LKB1 depletion from SC reduced lactate release (Beirowski, 2019), and in drosophila, LKB1 increases lactate transporter trafficking (Jang, Lee, & Chung, 2008). While the importance of lactate transfer from astrocytes to neurons to neuronal function and survival remains controversial (Magistretti & Allaman, 2018;Pellerin & Magistretti, 2012), evidence exists that in inactive MS lesions, a shift to increased glycolysis increases lactate shuttling between astrocytes and neurons, thought to be critical for the survival of demyelinated axons (Nijland et al, 2015).…”
Section: Astrocyte Metabolic Dysfunction Contribution To Disease Sesupporting
confidence: 85%
“…48 Others found that upregulating AMPK signaling-induced SCs proliferation and migration. 49,50 In this study, our loss-of-function study in AMPK signaling indicated that AMPK signaling had an important effect on SC proliferation and migration.…”
Section: Discussionmentioning
confidence: 69%